Evaluating effects of extreme rainfall on stormwater flows and water quality - Koh, Lin Yang (Nanyang Technological University, 2024)
Extreme rainfall can have profound effects on urban drainage infrastructure and water quality. Hence, it is important to evaluate these effects, especially in a high population density and large urban environment. By understanding these effects, proper mitigation strategies, such as low-impact developments can be implemented.